The Impact of Post-crisis Regulatory Architecture on Polish Cooperative Banks - Miklaszewska, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Cooperative banking – retail banking, carried out by locally-based small institutions, for years has played an important role in their local environments, enhancing bank reputation and trust. However, pre-crisis deregulation and the growing size and complexity of banking firms and post-crisis restructuring based on massive public assistance aimed at stabilizing the largest banks, create a hostile environment for locally based, small banks. Despite many declarations, the competitive, customer-friendly banking market is no longer a regulatory priority in the post-crisis era. Consequently, this paper analyses the relative position and future prospect of small banks, based on the example of Polish cooperative banking. It concentrates on the question of whether those banks are indirectly discriminated against and in which way the sector could be aided.